NOD2 activation enhances macrophage Fcγ receptor function and may increase the efficacy of antibody therapy - Merchand-Reyes, Giovanna; Bull, Mikayla F.; Santhanam, Ramasamy; Valencia-Pena, Maria L.; Murugesan, Rakesh A.; Chordia, Aadesh; Mo, Xiaokui-Molly; Robledo-Avila, Frank H.; Ruiz-Rosado, Juan De Dios; Carson, William Edgar; Byrd, John C.; Woyach, Jennifer A.; et al. (Frontiers in Immunology, 2024)
Therapeutic antibodies have become a major strategy to treat oncologic diseases. For chronic lymphocytic leukemia, antibodies against CD20 are used to target and elicit cytotoxic responses against malignant B cells. However, efficacy is often compromised due to a suppressive microenvironment that interferes with cellular immune responses. To overcome this suppression, agonists of pattern recognition receptors have been studied which promote direct cytotoxicity or elicit anti-tumoral immune responses. NOD2 is an intracellular pattern recognition receptor that participates in the detection of peptidoglycan, a key component of bacterial cell walls. This detection then mediates the activation of multiple signaling pathways in myeloid cells. Although several NOD2 agonists are being used worldwide, the potential benefit of these agents in the context of antibody therapy has not been explored. Here, we show that treatment of peripheral blood mononuclear cells with L18-MDP results primarily in the activation of monocytes. This was observed in cells from both healthy donors and CLL patients. Upon NOD2 stimulation, there was an upregulation of activating FcR in monocytes and a subsequent increase in antibody-mediated phagocytosis. This effect required the NF-κB and p38 signaling pathways. Using the E-TCL model of CLL, we found that combining NOD2 agonists with a murine anti-CD20 antibody led to a significant reduction of CLL load, as well as to a phenotypic change in splenic monocytes and macrophages. Taken together, these results suggest that NOD2 agonists help overturn the suppression of myeloid cells, and potentially augment the efficacy of antibody therapy for CLL.